Eksplorasi Kesulitan dan Kebutuhan Siswa dalam Pembelajaran Matematika di SMA Indocement - Fernando, Lukas; Putri, Nadia Arlisa; Nabila, Nazwa; Safitri, Sintia; Hernaeny, Ul’fah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research was conducted to explore the challenges and learning needs of students at SMA Indocement in mathematics education, as a foundation for improving the effectiveness of the learning process. A descriptive qualitative approach was used, with data collected through classroom observations, interviews with students and teachers, and documentation of student grades and Learning Objective Achievement Criteria (KKTP). The findings revealed that students struggle to understand new concepts and complex formulas, and they express a need for more engaging and interactive learning media. While PowerPoint presentations and random practice questions were considered helpful, students recommended incorporating digital platforms such as Kahoot and Quizizz to improve comprehension and engagement. Teachers were found to apply communicative and responsive teaching approaches. These results provide meaningful insights for developing more contextual and student-centered instructional strategies.